ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI PROVINSI JAWA TENGAH (Studi Kasus Pada Periode 2008-2021) - Utami, Astiti Margi; Pudjihardjo, M (Contemporary Studies in Economic, Finance and Banking, 2022)
The number of the workforce that is not proportional to the availability of jobs can lead to unemployment. In 2021, Central Java Province already has a dominant workforce from the total population so that it is vulnerable to unemployment. This research aims to analyze the effect of MSMEs, Investment and Minimum Wage on the unemployment rate in Central Java Province in 2008-2021. The method used in this study is quantitative analysis and used secondary data obtained from BPS, Central Java DPMPTSP, and other. The technique of analyzing data uses multiple regression with a supported by software SPSS. The resulth of the research show that : (1) number of MSMEs, Minimum Wage and investment had a significant affect simultaneously on unemployment rate (2) number of MSMEs had a negative and significant effect on unemployment rate (3) Minimum Wage had a positive and significant effect on unemployment rate (4) investment had no effect on unemployment rate. This is due to investment in Central Java Province which is concentrated in certain sectors that lead to capital-intensive industries so that investment does not have a significant effect on TPT.